(3EOGQI GdHfhcs - (3eMeO YHO GdaJGM(B, (3GdUjQajs ((3YeGf(B:s (3GdefGgL(B,s, 2006)
(3eGgjI GdHfc hhXGFag h CgOGag(B- (3GdJNWjW dGfTWI GdHfhc(B- (3JfXje GdHfhc GdJLGQjI h CNjQG GdQbGHI Ydi CfTWI GdHfhc (B.s
Keywords: (3GdGOGQIs; (3GdHfhcs; (3GdHfhc `` GOGQIs; (3GdHfhc GdJLGQjIs